Association of ‘Weekend Warrior’ Physical Activity Pattern and Depressive Symptoms - De Moraes-Ferrari, G (Elsevier B.V., 2025)
Background: Physical activity (PA) is recognized as a protective factor against depressive symptoms; however, the role of different PA patterns remains unclear. This study aimed to investigate the association between the “weekend warrior” PA pattern and depressive symptoms in the Brazilian population, with analyses stratified by sex and obesity status. Methods: This cross-sectional study analyzed data from 29,907 individuals aged 18 and older who underwent screening exams between 2008 and 2022 at a Brazilian hospital. PA was assessed using the long form of the International Physical Activity Questionnaire. Participants were grouped into three PA patterns: Not meeting PA recommendation (<150 min/week of moderate-to-vigorous PA), weekend warrior (≥150 min/week concentrated on 1–2 days), and regularly active (≥150 min/week on ≥3 days). Depressive symptoms were defined as a Beck Depression Inventory-II score ≥ 14. Logistic regression tested the associations in an unadjusted model and three adjusted models, controlling for sociodemographic, behavioral, and clinical variables. Results: The prevalence of depressive symptoms among participants was 10.4 %. The weekend warrior PA pattern was not associated with depressive symptoms. The regularly active PA pattern was associated with a lower likelihood of depressive symptoms (OR: 0.56; 95%CI: 0.52–0.61), and this association remained significant after adjustment across different models (OR: 0.68; 95%CI: 0.62–0.75). In the stratified analyses, no association was found between the weekend warrior PA pattern and depressive symptoms. Conclusion: The weekend warrior PA pattern was not associated with depressive symptoms, while the regularly active pattern was associated with lower odds, regardless of sex or obesity status. © 2025 Elsevier B.V.